2019
DOI: 10.3390/cancers11050669
|View full text |Cite
|
Sign up to set email alerts
|

Control of Tyrosine Kinase Signalling by Small Adaptors in Colorectal Cancer

Abstract: Tyrosine kinases (TKs) phosphorylate proteins on tyrosine residues as an intracellular signalling mechanism to coordinate intestinal epithelial cell communication and fate decision. Deregulation of their activity is ultimately connected with carcinogenesis. In colorectal cancer (CRC), it is still unclear how aberrant TK activities contribute to tumour formation because TK-encoding genes are not frequently mutated in this cancer. In vertebrates, several TKs are under the control of small adaptor proteins with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 138 publications
(151 reference statements)
1
6
0
Order By: Relevance
“…Consistently, our proteomic analyses uncovered several TKs, including ABL, activated by PEAK2 that would mediate its transforming activity, for which several inhibitors have been developed for the clinic (e.g., nilotinib, dasatinib and bosutinib). Our results predict inhibition of PEAK2 tumour activity by these therapeutic agents, which would also contribute to their antitumour effects reported in some CRC [ 50 , 55 , 56 ]. Collectively, our results suggest that PEAK2 pseudokinases could define attractive therapeutic targets in CRC, despite its catalytic inactivity.…”
Section: Discussionsupporting
confidence: 64%
“…Consistently, our proteomic analyses uncovered several TKs, including ABL, activated by PEAK2 that would mediate its transforming activity, for which several inhibitors have been developed for the clinic (e.g., nilotinib, dasatinib and bosutinib). Our results predict inhibition of PEAK2 tumour activity by these therapeutic agents, which would also contribute to their antitumour effects reported in some CRC [ 50 , 55 , 56 ]. Collectively, our results suggest that PEAK2 pseudokinases could define attractive therapeutic targets in CRC, despite its catalytic inactivity.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, it was reported that Src tumour activity is under the control of the Src-like adaptor protein SLAP [ 78 , 79 ] ( Figure 2 A,B). Such negative regulatory mechanism mediated by small adaptor proteins was originally described for the Janus Kinase (JAK)/STAT pathway, which it is mediated by the suppressors of cytokine signalling (SOCS) [ 80 ]. SLAP comprises an N-terminal region, similar to the one in Src, and a unique C-terminus with binding affinity to CBL.…”
Section: Sfks In Human Crcmentioning
confidence: 99%
“…Most CRC tumors have constitutive activation of transcription factors that activate inflammatory pathways, such as NF-κβ and the JAK-STAT pathway [ 25 ]. The JAK-STAT pathway is a major transducer of cytokine-signaling regulating inflammation and immune responses in CRC [ 26 ]. The JAK-STAT pathway is made of eight STAT proteins; primarily STAT-1 and -2 are involved in immune responses [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The JAK-STAT pathway is a major transducer of cytokine-signaling regulating inflammation and immune responses in CRC [ 26 ]. The JAK-STAT pathway is made of eight STAT proteins; primarily STAT-1 and -2 are involved in immune responses [ 26 ]. JAK-STAT activation is a notable characteristic of CMS1 as it displays strong immune activation [ 9 ].…”
Section: Resultsmentioning
confidence: 99%